Analisis Kebijakan Industrialisasi di Indonesia Mutakhir - Muchtar Ahmad (JIP ( Jurnal Industri dan Perkotaan ), 2009)
An image of no strategy of industrialization in Indonesia has stimulated this article, to discuss the contemporary industrial policy of Indonesia, especially post monetary and economy crises of 1998, which has been distort economic stability. The development of industrial policy and problems are analyzed, especially related to basic ideology, the goals and its achievement, in structural change and economic integration.  With this basic step, an industrialization policy system propose, which is planning as the institutional coordination of policies because industrialization should be based on agriculture toward agroindustry progress as the foundation of industrialization toward manufacturing, by mean of productivity increasing, purchasing power strengthen and improvement agriculture technology. In turn a policy of industrialization will be the development of import substitution industry and by proper selection the export –drive industry will be developed base on the criteria of jobs creation and economic structure change..